In vivo protective effect of lipopolysaccharide against Pseudomonas aeruginosa exotoxin A in mice. - Zehavi-Willner, T (1991)
Lipopolysaccharide (LPS) treatment of mice 1 to 5 days prior to administration of Pseudomonas aeruginosa exotoxin A (PA) induced full or partial protection against PA intoxication. The optimal LPS dose that induced resistance was 50 to 100 micrograms per mouse. Simultaneous administration of LPS and PA to mice, however, increased their sensitivity to PA two- to fourfold. Mice pretreated with LPS demonstrated a markedly enhanced clearance rate of 125I-labeled PA from peripheral blood, livers, and kidneys. In mice exposed to LPS and PA simultaneously, the rate of elimination of labeled PA was lower than that in control mice. While protein synthesis was inhibited significantly in livers and other organs of PA-exposed mice, in LPS-pretreated mice, PA-induced inhibition of protein synthesis was either diminished or totally prevented and elongation factor 2 (EF2) levels were normal. In mice treated only with LPS, enhanced protein synthesis and increased levels of EF2 were observed, suggesting that LPS protection against PA intoxication was perhaps a consequence of excessive amounts of EF2 induced by LPS.